The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1977
DOI: 10.1128/aac.11.6.999
|View full text |Cite
|
Sign up to set email alerts
|

Mercury Resistance and R Plasmids in Escherichia coli Isolated from Clinical Lesions in Japan

Abstract: The mercury and antibiotic resistance of 338 strains of Escherichia coli isolated from hospital patients was determined. Resistance to mercury was found in 58.6% of the isolates. The frequencies of resistance to streptomycin (Sm), tetracycline (Tc), chloramphenicol (Cm), kanamycin (Kan), cephaloridine (Cer), and gentamicin (Gm) were 66.3,60.3, 56.5, 42.9, 32.1, and 1.5%, respectively. Among the above, 198 mercury-and antibiotic-resistant isolates were selected and tested for their ability to transfer the resis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
25
1

Year Published

1982
1982
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 22 publications
1
25
1
Order By: Relevance
“…Similar results (196) showed that 12.8% of 148 clinical E. coli isolates selected for their elevated chlorhexidine MICs were no less susceptible to use concentrations. Such changes, in the case of the Providencia isolates, were thought to affect binding of the biguanides to the cell surface and therefore reflected envelope modification (74).…”
Section: Possible Associations Between Biocide Use and Resistance-fiesupporting
confidence: 72%
“…Similar results (196) showed that 12.8% of 148 clinical E. coli isolates selected for their elevated chlorhexidine MICs were no less susceptible to use concentrations. Such changes, in the case of the Providencia isolates, were thought to affect binding of the biguanides to the cell surface and therefore reflected envelope modification (74).…”
Section: Possible Associations Between Biocide Use and Resistance-fiesupporting
confidence: 72%
“…This was confirmed by the lack of amplification of mer A or mer R genes using plasmid DNA as a template. Our results contrast with reports in literature where mer operons reside frequently in plasmids (Nakahara et al , 1977). Previous work in our laboratory searching for Class 1 integrons revealed also a preferential chromosomal vs. plasmid localization of these elements in Aeromonas spp.…”
contrasting
confidence: 99%
“…48 In the first 5 days of reacting divalent Hg with L-cysteine ethyl ester (L-CysOEt) at a ratio of 1:2 in water equilibrated with air or purged with argon at RT, a whitish suspension progressively formed ( Figure 3D). Between 5 and 19 days, the suspensions darkened in color to black.…”
Section: Environmental Science and Technologymentioning
confidence: 98%